2018
DOI: 10.1016/j.jfma.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Review of underactive bladder

Abstract: In clinical practice, many patients cannot empty their bladders within an acceptable duration. Common complaints include weak urinary stream and incomplete emptying, which may affect quality of life. Bladder emptying requires sufficient detrusor contractile power, velocity, and durability. The urodynamic term for inadequate detrusor contraction is detrusor underactivity (DU). Although this definition was provided by the ICS, it may not be clinically practical. Analogous to the relationship between overactive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
0
17
0
7
Order By: Relevance
“…According to these criteria, BCI <100 corresponds to weak detrusor, between 100-150, normal detrusor, and >150, strong detrusor (12). As observed in Table 2, there is a statistically difference between the groups for BCI, showing that this could be a good parameter, in opposition to what has been presented in other articles that BCI is not able to differentiate patients with DU from those with BOO (8,20).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…According to these criteria, BCI <100 corresponds to weak detrusor, between 100-150, normal detrusor, and >150, strong detrusor (12). As observed in Table 2, there is a statistically difference between the groups for BCI, showing that this could be a good parameter, in opposition to what has been presented in other articles that BCI is not able to differentiate patients with DU from those with BOO (8,20).…”
Section: Discussionmentioning
confidence: 79%
“…One study compared Schafer Nomogram, BCI and WF, and showed that only Schafer Nomogram would be able to identify BOO, however, we could observe from the data presented that both BCI and WF were able to differentiate DU from BOO (8).…”
Section: Variablesmentioning
confidence: 71%
See 1 more Smart Citation
“…Already recognized mechanisms underlying DU include degeneration of bladder smooth muscle cells, disorders affecting central nervous system control of the voiding reflex, and disruption of the efferent–afferent nerves of the lower urinary tract . A less explored mechanism is modification of the urethra–bladder reflex .…”
Section: Introductionmentioning
confidence: 99%
“…2 Already recognized mechanisms underlying DU include degeneration of bladder smooth muscle cells, 3 disorders affecting central nervous system control of the voiding reflex, and disruption of the efferent-afferent nerves of the lower urinary tract. 4 A less explored mechanism is modification of the urethra-bladder reflex. 5,6 Urethral anesthesia with lidocaine inhibits subepithelial afferent nerves and prevents the occurrence of effective bladder contractions in humans and other mammals.…”
mentioning
confidence: 99%